2020
DOI: 10.1021/acs.cgd.0c00123
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Biarsenate Capped Keggin Arsenomolybdates with Tetravanadium Substitution for Photocatalytic Degradation of Organic Dyes

Abstract: Four new POMs biarsenate­(III) capped Keggin arsenomolybdates with tetravanadium­(IV) substituted (bix)­[H3As2 IIIAsVMo8V4 IVO40]­[Cu­(bix)]2·3H2O­(1), [{HAs2 IIIAsV Mo8V4 IVO40}­{Cu­(bib)}2]­[Cu­(bib)]2(2), [{As2 IIIAsVMo8V4 IVO40}­{Cu3(tib)2(H2O)2}] [Cu­(tib)­(H2O)]2·4H2O­(3), and [HAs2 IIIAsVMo8V4 IVO40]­[Cu2(bih)]2(4) (bix = 1,4-bis­(imidazol-1-ylmethyl) benzene; bib = 1,3-bis (imidazol-1-ylmethyl)­benzene; tib = 1,3,5-tris­(1-imidazolyl)­benzene; bih = 1,6-bis­(imidazol-1-ylmethyl)­hexane) were prepared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…31 The apparent absorption bands in the 1200−1600 cm −1 region are assigned to CC and CN of ligand bix. 32 The bond valence sum (BVS) 33 calculations of the V-Zn-MOF reveal that the oxidation states of all V atoms and Zn atoms are +5 and +2, respectively (Table S3). In addition, the XPS experiment of the V-Zn-MOF is carried out to further determine the oxidation states of V and Zn atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…31 The apparent absorption bands in the 1200−1600 cm −1 region are assigned to CC and CN of ligand bix. 32 The bond valence sum (BVS) 33 calculations of the V-Zn-MOF reveal that the oxidation states of all V atoms and Zn atoms are +5 and +2, respectively (Table S3). In addition, the XPS experiment of the V-Zn-MOF is carried out to further determine the oxidation states of V and Zn atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Experimental and theoretical studies of arsenomolybdates photocatalysis have revealed that it typically proceeds based on the following mechanism [41,42,48,52]: Irradiated of arsenomolybdates by UV light with energy equal to or greater than the E g value of itself, which induces intramolecular charge-transfer from the HOMO of O to the LUMO of Mo, leading to the formation of photoexcited states, subsequently photogenerated electron-hole pairs were generated. The O 2 captures electron to form • O 2ˉa nd the hole reacts with H 2 OorOH À ions to form • OH.…”
Section: Reaction Mechanisms Of Photocatalytic Performancementioning
confidence: 99%
“…Some research data show that the samples were washed and dried after the arsenomolybdates as photocatalysis several cycles, and the infrared or X-ray diffraction test were carried out, the infrared spectra or X-ray diffraction data of arsenomolybdates demonstrate that there are almost unchanged before and after photocatalytic reaction [44][45][46][47][48], which indicate that arsenomolybdates photocatalysis have excellent structural stability.…”
Section: Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, only a few cases have been reported with the timb ligand utilized for building POMbased framework materials. [30][31][32] Based on the above considerations, 1,3,5-tris(1-imidazolyl) benzene and Na 2 WO (3). The different structures are discussed, of which compound 1 exhibits a rare 3,6-connected pyr topology, compound 2 displays a rare 3D structure accumulated via two different 2D layers in the BBABB mode and a variety of hydrogen bonding interactions link 1D chains into a 3D network in compound 3.…”
Section: Introductionmentioning
confidence: 99%